Implementation of the Distribution Requirement Planning Method in Optimizing the Distribution of Packaged Drinking Water Products - Nurlaila Handayani; Yusri Nadya; Dwi Maulana (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
CV Athaya Mineral is an industry that runs its business in the production and distribution of bottled drinking water. At the time of distribution of its products, errors often occur, namely the interpretation of demand data in each distribution chain and information received. The purpose of this study was to determine the optimal lotting technique for the distribution of these products using the Distribution Requirement Planning (DRP) method. From the results of data processing, the retail value of Kede Osa was obtained with a total cost of Rp. 233.696, New Store retail with an amount of Rp. 417,336, retail Ari JP Rp. 99,727, Simpang Remi retail Rp. 165,140, retail Mita Jaya Rp. 619,981. The conclusion of this study is the distribution of the Distribution Requirement Planning method for all Dance products (Glass, Small Bottles, Medium Bottles, and Gallons) to five retailers (Kede Osa, Toko Baru, Ari JP, Simpang Remi, and Mita Jaya) using Economic Order Quantity (EOQ) is a lotting technique with the cheapest distribution costs, except for New Store retailers using the Lot For Lot (LFL) lotting technique.